A model for yellow fever with migration. Issue 6 (16th August 2019) - Esteva, Lourdes; Vargas, Cristobal; Yang, Hyun Mo
Abstract : In this work, we formulate a mathematical model to evaluate the risk of the introduction of yellow fever (YF) in towns by infected humans arriving from forest areas. We obtain the basic reproduction numbers associated with the forest and urban regions. We present numerical simulations to evaluate the risk of YF spread for different migration rates.